Supporting breastfeeding: Tanzanian men's knowledge and attitude towards exclusive breastfeeding - Janeth Bulemela; Heka Mapunda; Erna Snelgrove-Clarke; Noni MacDonald; Robert Bortolussi (BMC, 2019)
Abstract Background Exclusive breastfeeding (EBF) is one of the key strategies to ensure infants and young children survive and grow. However, a 2010 study showed that it was only practiced by 50% of Tanzanian women. That study also found that men were rarely supportive; either at home or in the health facilities, due to their personal beliefs or to traditional beliefs and culture of the community. In a report six years later the rate of EBF has decreased to 30%, in one region. Methods In this qualitative study, we used focus groups to assess the knowledge and attitudes of 35 men from three villages on the benefits of EBF, the disadvantages of not breastfeeding, and how they can support their partners' breastfeeding. In addition, we assessed how they felt about spending time at home, if they considered handling the infant to be rewarding and whether they helped the mother with home chores. Differences in village infrastructure and characteristics were noted. Results Five themes were identified, including traditional roles, and feelings of exclusion/inclusion and resistance. Men felt they needed better information on EBF. They wished that their partners could breastfeed for a longer time, since they realized it improved infant growth and prevented disease; however, they did not have time to remain with the infant at home. Poverty required the men to work for long periods outside the home. As well, the men were not involved with the Reproductive Child Health Clinic (RCHC) except at the time of delivery or for mandatory HIV testing, however, they wanted to be educated together with their partners at the RCHC. Conclusion Most men in this study understood that the EBF period was important, and that it broadened their relationship with their partner. EBF, however, could be a challenge for couples because of poverty. Nevertheless, many men wanted to help and to become more involved.